2016
DOI: 10.1002/2016jd025142
|View full text |Cite
|
Sign up to set email alerts
|

Polarimetric radar characteristics of storms with and without lightning activity

Abstract: This paper analyzes the cloud microphysics in different layers of storms as a function of three‐dimensional total lightning density. A mobile X‐band polarimetric radar and very high frequency (VHF) sources from Lightning Mapping Array (LMA) observations during the 2011/2012 Brazil spring‐summer were used to determine the microphysical signatures of radar vertical profiles and lightning density. This study quantified the behavior of 5.3 million vertical profiles of the horizontal reflectivity (ZH), differential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 76 publications
2
19
0
2
Order By: Relevance
“…These layers were chosen due to the different physical behaviors related to the thunderstorm electrification process observed by Mattos et al . []. Figure presents the whisker plots for all four thunderstorm layers in the four different lifetimes.…”
Section: Statistical Evaluation Of the 46 Thunderstormsmentioning
confidence: 99%
See 3 more Smart Citations
“…These layers were chosen due to the different physical behaviors related to the thunderstorm electrification process observed by Mattos et al . []. Figure presents the whisker plots for all four thunderstorm layers in the four different lifetimes.…”
Section: Statistical Evaluation Of the 46 Thunderstormsmentioning
confidence: 99%
“…Many works have demonstrated that electric fields in clouds can also influence the orientation of ice crystals with oblate and prolate shapes [Weinheimer and Few, 1987;Metcalf, 1993Metcalf, , 1995Krehbiel et al, 1996;Caylor and Chandrasekar, 1996;Metcalf, 1997;Foster and Hallett, 2002;Ventura et al, 2013;Mattos et al, 2016]. In conditions of strong electric field ice crystals are mostly vertically oriented.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also the 75th percentile retains information about the storm even if the convection is relatively shallow, whereas the median must have a storm of at least 6 km depth before showing a signal. Ignoring the data below 2.5 km eliminates the potentially misleading FIGURE 1 The accumulated rainfall from the radar composite on August 31, 2017 from 1200 to 1300, black crosses show the location of lightning strikes intensification of the melting layer (e.g., at 153 km in the top right panel of Figure 2) which contains little information about the microphysics of a thunderstorm (Mattos et al, 2016). It can be seen in Figure 2 that the more convective (1135 and 1140) timestamps have a smaller difference between the entire column method (the black line) and the above the melting layer method (the red line) than the more stratiform timestamp (1130).…”
Section: Storm Trackingmentioning
confidence: 99%